Diagnosis of Pregnancy and Uterine Infections by Ultrasound During out Breeding in Saanen Goats in Halabja Province, Kurdistan, Iraq - Talib Ghaidan (مجلة الانبار للعلوم البيطرية, 2023)
The aim of this study is to find out the incidence of pregnancy and some uterine diseases, such as hydrometra and mucometra in female Saanen goats out of seasonal breeding by using ultrasound scanning. This study was conducted in January 2022 in field of Saanen goats in Halabja province / Kurdistan Region. Out of 120 examination of female Saanen goats, the investigation were recorded 8 (6.7%) for pregnant, 80 (66.7%) non pregnant and 2 (1.6%) abortion whereas 18 (15%) and 12 (10%) for hydrometra and mucometra respectively. The previous conditions of infected uterus are considered a pseudopregnancy in goats according to the many researchers. In addition to these uterine infections are causes temporary infertility in goats.Therefore, it is preferable to treat such cases as soon as possible using hormones such as PGF2α. Finally it concluded that real-time ultrasound is considered rapid, precise, and accuracy device used for diagnosis of pregnancy and reproductive disorders represented by hydrometra and mucometra in goats.